How does high-intensity intermittent training affect recreational endurance runners? Acute and chronic adaptations: A systematic review - García-Pinillos, Felipe (J Sport Health Sci, 2017)
OBJECTIVE: This systematic review aimed to critically analyze the literature to determine how high-intensity intermittent training (HIIT) affects recreational endurance runners in the short- and long-term. METHODS: Electronic databases were searched for literature dating from January 2000 to October 2015. The search was conducted using the key words “high-intensity intermittent training” or “high-intensity interval exercise” or “interval running” or “sprint interval training” and “endurance runners” or “long distance runners”. A systematic approach was used to evaluate the 783 articles identified for initial review. Studies were included if they investigated HIIT in recreational endurance runners. The methodological quality of the studies was evaluated using the Physiotherapy Evidence Database (PEDro) scale (for intervention studies) and the modified Downs and Black Quality Index (for cross-sectional studies). RESULTS: Twenty-three studies met the inclusionary criteria for review. The results are presented in 2 parts: cross-sectional (n = 15) and intervention studies (n = 8). In the 15 cross-sectional studies selected, endurance runners performed at least 1 HIIT protocol, and the acute impact on physiological, neuromuscular, metabolic and/or biomechanical variables was assessed. Intervention studies lasted a minimum of 4 weeks, with 10 weeks being the longest intervention period, and included 2 to 4 HIIT sessions per week. Most of these studies combined HIIT sessions with continuous run (CR) sessions; 2 studies' subjects performed HIIT exclusively. CONCLUSION: HIIT-based running plans (2 to 3 HIIT sessions per week, combining HIIT and CR runs) show athletic performance improvements in endurance runners by improving maximal oxygen uptake and running economy along with muscular and metabolic adaptations. To maximize the adaptations to training, both HIIT and CR must be part of training programs for endurance runners.